Peripartum cardiomyopathy: an obstetric review - Sharma, Priyanka; Kumar, Binay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Peripartum cardiomyopathy (PPCM) is a rare and potentially fatal form of systolic heart failure which presents in later months of pregnancy and post-partum. Incidence varies over geography and ethnicity. It is highest in the African tribes of Hausa and Fulani. The incidence in the United States ranges from 1 in 1500-7500 births. Risk factors include advanced maternal age, multiparity, preeclampsia, multifetal gestation and African descent. Various etiologies such as viral myocarditis, abnormal immune and hemodynamic response to pregnancy, inflammatory mediation and genetic susceptibility have been proposed. Of late, the role of abnormal prolactin metabolism and resulting myocardial toxicity have been explored and bromocriptine has shown promise as a potential treatment option. Medical management is similar to other causes of systolic heart failure, except that ACE inhibitors and angiotensin receptor blockers are avoided in pregnancy. Complications include cardiac arrhythmias, thromboembolism and refractory heart failure can occur. Maternal deaths are not uncommon.